Simulation and economic assessment of using H₂O₂ solution in wet scrubber for large marine vessels. (1st March 2020) - Choi, Yeongryeol; Kim, Junghwan; Moon, Il
Abstract: As emission regulation for marine vessels has become strict since 2016, a new emission control method is required. This paper proposes using the H₂O₂ solution in a wet scrubber for SOx and NOx removal for a conventional large marine vessel that uses a low-speed two-stroke diesel engine and a heavy fuel oil, and aims to evaluate the economic feasibility of this approach compared with other methods. Measurement data for the exhaust gas of the engine are incorporated in a process simulation based on physical properties and kinetics that relate H₂O₂ with emission materials. H₂O₂ consumption rate is determined to be 757.38 and 10.37 kg/h, depending on sailing in an emission control area or not. The parameters for techno-economic analysis are based on capital cost, operating cost, sailing information, and fuel cost in January 2018. The net present value of the proposed method is calculated to be 3.26% higher than other methods, and the proposed method is more economical than other methods when the sailing ratio in the emission control area is less than 75.98%. Based on these results, the proposed method can be utilized as an alternative emission control method for a marine vessel that considers retrofitting to satisfy strict emission regulations. Highlights: Simulation and TEA were conducted for H₂O₂ in wet scrubber of a marine vessel. H₂O₂ consumption rates were calculated to be 757.38 and 10.37 kg/h, respectively. The NPV of the proposed method was calculated as 596.682 MUSD. This method was more economical than others when the ECA ratio was below 75.98%.